Diagnostic accuracy of ECG smart chest patches versus PPG smartwatches for atrial fibrillation detection: a systematic review and meta-analysis - Olivier Sibomana; Clyde Moono Hakayuwa; Abraham Obianke; Hubert Gahire; Jildas Munyantore; Matimba Molly Chilala (BMC Cardiovascular Disorders)
Abstract Introduction Atrial fibrillation (AF), the most common form of cardiac arrhythmia, is associated with significant morbidity, mortality, and financial burden. Traditional diagnostic methods, such as 12-lead electrocardiograms (ECG), have limitations in detecting intermittent AF episodes. Consequently, smart wearables have been introduced to enhance continuous AF monitoring. This systematic review and meta-analysis aimed to evaluate and compare the diagnostic accuracy of ECG smart chest patches and photoplethysmography (PPG)– based smartwatches in AF detection. Methods From august 16–20, 2024, a comprehensive search was conducted across PubMed/MEDLINE, DOAJ, AJOL, and the Cochrane Library. Original studies assessing the performance of ECG smart chest patches and PPG smartwatches in detecting AF were included. Studies were screened based on predefined inclusion and exclusion criteria, and the most relevant were finally included. For ECG smart chest patches and PPG smartwatches groups, random-effects model was used to pool these performance metrics. Statistical analyses were performed using Jamovi 2.3.28, with a significance threshold of p < 0.05. Results A total of 15 studies were included in the current systematic review and meta-analysis. ECG smart chest patches demonstrated a pooled sensitivity of 96.1% [(95% CI: 91.3–100.8), (I² = 94.59%)], and a pooled specificity of 97.5% [(95% CI: 94.7–100.2), (I² = 79.1%)]. PPG smartwatches showed a pooled sensitivity of 97.4% [(95% CI: 96.5–98.3), (I² = 3.16%)], and a pooled specificity of 96.6% [(95% CI: 94.9–98.3), (I² = 75.94%)]. Comparatively, both ECG smart chest patches and PPG smartwatches exhibited excellent performance in atrial fibrillation detection, with PPG smartwatches showing slightly higher sensitivity and ECG chest patches exhibiting marginally greater specificity. Conclusion Both ECG smart chest patches and PPG smartwatches are highly effective for detecting atrial fibrillation. However, further advancements are needed to match their accuracy with that of standard diagnostic methods and achieve comprehensive digital cardiac monitoring.